(3eHGOF h eOGNd GdGOGQI h hXGFagG aj GdbQf GdMGOj h GdYTQjfs - (3RcQjG(B, (3GdOhQjs; (3GdYRGhj fLe(B, (3GdScGQfI HdGd Ndas ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2010)
(3GSGSjGJ GdGOGQI , JWhQ GdacQ GdGOGQj , GdJNWjW , GdJUeje GdJfXjej , GdJhLjg (B( (3GdGJUGd , GdbjGOI , GdJMVjQ (B) (3, GdQbGHI GdGOGQjI , GdeOGNd GdGNdGbjI h GdeYQajI aj GOGQI GdefXeGJ , GdeNGd GdJbfjI GdeYGUQI aj GOGQI GdefXeGJs
(3eQGLY U(B.423 (3;GdLOGhd U(B.212 (3,(B311s
Keywords: (3EOGQI GdCYeGds; (3GdEOGQIs; (3GdQbGHI GdGOGQjIs